STRATEGI PEMBELAJARAN INKUIRI JURISPRUDENSIAL DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN PADA MAHASISWA PGSD FKIP UNSRI - nuraini usman (Jurnal Inovasi Sekolah Dasar, 2015)
Abstract:Research objectives to improve the quality of learning citizenship education.The subject of research is a student PGSD  FKIP UNSRI a total of 44 were, 2 men, 41 people extent are women 's that follows a course called the basic concept of pkn first semester.Campus research locations PGSD Universitas Sriwijaya.RoadsA gatherer of engineering data in the form of, the results of duty, make klipping about a case (problems / violation of law the value of a norm) the source of a newspaper, magazine and the internet , an analysis of duty, skill assessment question and answer session , the assessment of the presentation of the group and the test results analyzed by technique qualitative and quantitative.Conclusion in research Conclusion in this research strategy learning inkuiri jurisprudensial will increase the quality of learning. Keywords:Strategy LearningInquiry, jurisprudential,MoralvaluesLaw.  Abstrak: Tujuan penelitian untuk meningkatkan kualitas pembelajaran pendidikan kewarganegaraan. Subyek penelitian adalah mahasiswa PGSD FKIP UNSRI berjumlah 44 orang, 2 orang laki-laki, 41 perempuan yang mengikuti mata kuliah Konsep Dasar PKn semester satu. Lokasi penelitian Kampus PGSD Universitas Sriwijaya. Teknik pengumpul data berupa hasil tugas, membuat klipping tentang sebuah kasus (permasalahan pelanggaran hukum/nilai/norma) sumber dari koran, majalah dan internet, analisis tugas, penilaian keterampilan tanya jawab, penilaian presentasi kelompok dan tes hasil belajar.Data dianalisis dengan teknik kualitatif dan kuantitatif.Kesimpulan dalam penelitian ini strategi pembelajaran InkuiriJurisprudensial dapat meningkatkan kualitas pembelajaran. Kata Kunci: Setrategi PembelajaranInkuiri, Jurisprudensia, Nilai-nilai Moral Hukum